2020
DOI: 10.18332/ejm/120116
|View full text |Cite
|
Sign up to set email alerts
|

Birth preparedness, utilization of skilled birth attendants and delivery outcomes among pregnant women in Ogun State, Nigeria

Abstract: INTRODUCTION Birth preparedness and complication readiness (BPCR) is an approach initiated to facilitate utilization of skill birth attendants (SBAs) for improved pregnancy outcomes. Despite its usefulness, many women still did not use skilled birth attendants. The purpose of this study is to assess the level of birth preparedness and complication readiness and its association with skilled birth attendants’ utilization. METHODS A descriptive sequential mixed methods des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…This was in agreement with the findings of a study in northern Nigeria 27 but in consonance with another study in southern Nigeria. 14 Similarly, trends in SBA use were insignificant at higher birth orders but significant for lower birth orders. Trends in SBA use was also significant among women with adequate ANC visit and when both respondent and spouse decide on the woman's healthcare.…”
Section: Open Accessmentioning
confidence: 96%
“…This was in agreement with the findings of a study in northern Nigeria 27 but in consonance with another study in southern Nigeria. 14 Similarly, trends in SBA use were insignificant at higher birth orders but significant for lower birth orders. Trends in SBA use was also significant among women with adequate ANC visit and when both respondent and spouse decide on the woman's healthcare.…”
Section: Open Accessmentioning
confidence: 96%
“…Studies have reported that wealth, education, type of residence among others are associated with the underutilization and utilization of ANC in Nigeria [21][22][23]. Literatures on SBA use in Nigeria highlighted births preparedness, ANC visit, pregnancy complications and women's involvement in healthcare decisions as major determinants [13,[24][25][26]. The effect of both ANC and SBA utilization on PNC uptake has been reported [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Though studies have independently investigated ANC, SBA and PNC in Nigeria [21][22][23][24][25][26]34], there is however paucity of information on the linkage among the three pillars of maternity CoC. Although Akinyemi et al assessed dropout, the study did not consider the recommended optimal number of ANC contacts and the pregnancy-related factors [6].…”
Section: Introductionmentioning
confidence: 99%
“…Literatures has widely documented that sociodemographic, reproductive, and other maternal health factors are associated with utilization of maternal health care services [ 16 – 21 ] in SSA. This includes the antenatal care uptake [ 14 , 22 , 23 ], skilled provider use [ 24 26 ], and utilization of postnatal care services [ 27 29 ]. Also, women continuity of the maternity health care continuum (from antepartum to postpartum) has been studied [ 30 32 ].…”
Section: Introductionmentioning
confidence: 99%